Offspring beg more toward larger females in a burying beetle. (11th September 2020) - Ratz, Tom; Stenson, Sophie; Smiseth, Per T
Abstract: Offspring of many animals beg for food from parents. Begging is often costly, and offspring should seek to reduce such costs to maximize their returns on begging. Whenever multiple adults provide care for a joint brood, as in species where multiple females breed communally, offspring should beg toward the parent that provisions the most food. Here, we investigate whether larvae spend more time begging toward larger females in the burying beetle Nicrophorus vespilloides . Prior work on this species shows that larger females provision more food than smaller ones, suggesting that larvae would benefit by preferentially begging toward larger females. To test for such a preference, we provided experimental broods with a simultaneous choice between two dead females: a smaller and a larger one. Larvae spent more time begging toward larger females. We next examined the behavioral mechanism for why larvae begged more toward larger females. Larvae spent more time in close contact with larger females over smaller ones, whereas there was no evidence that larvae begged more when in close contact with larger females. Thus, larvae begged more toward the larger female simply as a consequence of spending more time close to larger females. Our findings have important implications for our understanding of parent–offspring communication by showing that offspring can choose between parents based on parental attributes, such as body size, reflecting how much food parents are likely to provision. Abstract : To maximize their returns on begging, offspring should beg toward the parent that provisions more food, such as the larger parent. We tested this prediction using a burying beetle and found that offspring beg more toward larger parents as a result of spending more time near larger parents. Our findings show that offspring can assess a difference in body size between two parents and adjust their behavior accordingly.